1980
DOI: 10.1136/sti.56.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus hominis type 2 infection in Ibadan. Problem of non-venereal transmission.

Abstract: SUMMARY Examination of sera from blood donors, from patients attending a special treatment clinic, a family planning clinic, and an antenatal clinic showed that the prevalence of herpesvirus hominis type 2 antibodies among the adult population in Ibadan is similar to that in other parts of the world.The possibility of non-venereal transmission of herpesvirus infection was confirmed by the finding that herpesvirus hominis type 2 could survive on cloth samples under humid tropical conditions for long enough to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Our study showed no acquisition of herpes simplex virus type 2 infection in Navajo children, a finding consistent with reports from a sample of urban children in Atlanta, Georgia (30). Studies in Delhi, India (29), in Nigeria (31,32), and of Indian tribes in Brazil (25) reported acquisition of these antibodies in children, suggesting routes of nonsexual transmission in these populations. However, the antibody assays employed in these earlier studies (complement fixation or microneutralization) were not adequately specific to the herpes simplex virus antibodies, leaving the findings in doubt.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed no acquisition of herpes simplex virus type 2 infection in Navajo children, a finding consistent with reports from a sample of urban children in Atlanta, Georgia (30). Studies in Delhi, India (29), in Nigeria (31,32), and of Indian tribes in Brazil (25) reported acquisition of these antibodies in children, suggesting routes of nonsexual transmission in these populations. However, the antibody assays employed in these earlier studies (complement fixation or microneutralization) were not adequately specific to the herpes simplex virus antibodies, leaving the findings in doubt.…”
Section: Discussionsupporting
confidence: 91%
“…This is supported by observations that antibodies to HVH-2 only begin to appear after the age of 15 years18 and are particularly common in the sexually promiscuous.19 However genital herpetic infections do occur in children9-10 and both strains of HVH have been implicated in their causation.1" In poor socioeconomic populations HVH-1 antibodies are soon acquired after the first year of life.15 The HVH-2 infections in children are believed to be largely nonvenereal and are similarly most likely to occur in conditions of overcrowding and poor personal hygiene." -15 A similar sort of setting has been adduced to be responsible for the nonsexual spread of gonococcal vulvovaginitis in young girls in Ibadan, Nigeria.20 Recent studies by Montefiore et al 21 showed that HVH-2, under humid tropical conditions, can survive sufficiently long on cloth to facilitate transmission of infection by fomites such as shared bed-clothes, towels, or underwear. Communal use of such articles is common in many poor families in tropical Africa, and it is in such households that protein-energy malnutrition is prevalent.…”
Section: Discussionmentioning
confidence: 99%